Synthesis and Characterization of Leaf-Like CuO Nanostructures - Ding, Aiqin; Deng, Chonghai; Han, Chengliang; Xie, Jinsong; Yang, Benhong (Asian Journal of Chemistry, 2014)
Using copper chloride and triethylamine as starting reactants, uniform two dimensional (2D) leaf-like CuO nanostructures have been successfully prepared via a convenient microwave-assisted chemical route. The synthesized products were characterized by X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM) and UV-visible absorption spectrum. The widths of the central parts for shuttle-like CuO nanoleaves are estimated to be 100-160 nm and the lengths are 0.8-1.4 μm. The growth process of leaf-like CuO nanostructures was investigated in detail. The band-gap energy of as-prepared CuO nanoleaves was estimated to be 2.56 eV from the optical absorption spectrum, showing a good quantum size effect.